A biomarker panel and psychological morbidity differentiates the irritable bowel syndrome from health and provides novel pathophysiological leads. Issue 4 (6th January 2014) - Jones, M. P.; Chey, W. D.; Singh, S.; Gong, H.; Shringarpure, R.; Hoe, N.; Chuang, E.; Talley, N. J.
Summary Backgrounds The development of a reliable biomarker for irritable bowel syndrome (IBS) remains one of the major aims of research in functional gastrointestinal disorders (FGIDs) and is complicated by the absence of a perfect reference standard. Previous efforts based on genetic and immune markers have showed promise, but have not been robust. Aim To evaluate an extensive panel of gene expression and serology markers combined with psychological measures in differentiating IBS from health and between subtypes of IBS. Methods Of subjects eligible for analysis (N = 244), 168 met criteria for IBS (60 IBS‐C, 57 IBS‐D and 51 mixed), while 76 were free of any FGID. A total of 34 markers were selected based on pathways implicated in pathophysiology of IBS or whole human genome screening. Psychological measures were recorded that covered anxiety, depression and somatisation. Models differentiating disease and health were based on unconditional logistic regression and performance assessed through area under the receiver‐operator characteristic curve (AUC), sensitivity and specificity. Results The performance of a combination of 34 markers was good in differentiating IBS from health (AUC = 0.81) and was improved considerably with the addition of four psychological markers (combined AUC = 0.93). Of the 34 markers considered, discrimination was derived largely from a small subset. Good discrimination was also obtained between IBS subtypes with the best being observed for IBS‐C vs. IBS‐D (AUC = 0.92); however, psychological variables provided almost no incremental discrimination subtypes over biological markers (combined AUC = 0.94). Conclusions A combination of gene expression and serological markers in combination with psychological measures shows exciting progress towards a diagnostic test for IBS compared with healthy subjects, and to discriminate IBS‐C from IBS‐D.